Cefiderocol use in Gram negative infections with limited therapeutic options: Is combination therapy the key? - Silvia Corcione; Ilaria De Benedetto; Simone Mornese Pinna; Davide Vita; Tommaso Lupia; Giorgia Montrucchio; Luca Brazzi; Francesco Giuseppe De Rosa (Elsevier, 2022)
Objectives: To date limited information about cefiderocol use is provided by real life studies. Our aim is to evaluate characteristics and outcome of patients with Gram-negative infections with limited therapeutic options treated with cefiderocol in combination or monotherapy. Methods: We retrospectively collected data on demographical, clinical characteristics and clinical cure, in-hospital and 30-days mortality, microbiological failure and Clostridioides difficile infections of all patients ≥ 18 years old treated with cefiderocol for ≥ 48 h. Results: There were 18 patients of which 14 (77.8%) treated with cefiderocol in combination and 4 (22.2%) with monotherapy. Median age was 54.5 (IQR 35.25-65.75) vs 70.5 (IQR 57.5-78.25) years old, respectively and ward of admission was the ICU in the 78.57% vs 100% of cases. In the 50% vs 100% of cases infections were VAP with concomitant bloodstream infections. Median SOFA score was 10 (IQR 4.5-12.5) vs 5 (IQR 4-6) and APACHE II score was 13.5 (IQR 7.5-18) vs 16 (IQR 8.5-23.5), respectively. Isolated pathogen was carbapenems-resistant Acinetobacter baumannii in 78.57% vs 100% of cases. Median duration of cefiderocol treatment was 9.5 (IQR 7-13.25) vs 9 days (IQR 5.5-12.5) and in 77.8% patients it was used in combination therapy, of which 57.1% were colistin-spairing regimens. Clinical cure was achieved in 64.29% for combination therapy vs 75% of monotherapy treated patients, 30-days mortality rate was 28.57% vs 25% and 30-day ICU admission rate was 14.29% vs 50%, respectively. No statistically significant differences were observed between combination therapy and monotherapy treated patients. Conclusions: To date, no differences have been demonstrated between cefiderocol monotherapy or combination. Further studies are required to understand whether cefiderocol combination therapy could provide an advantage in outcome in seriously-ill patients.